ANALISIS PENGARUH KUALITAS LAYANAN, PERSEPSI HARGA DAN CITRA PERUSAHAAN TERHADAP KEPUASAN DAN DAMPAKNYA PADA LOYALITAS KONSUMEN DI MATAHARI DEPARTMENT STORE PARAGON CITY MALL SEMARANG - Eka Lestari, 12.05.51.0025; Rizal Riva'i, Alimuddin (Students' Journal of Economic and Management, 2016)
The purpose of this study was to analyze the influence of service quality, perceived price, corporate image on customer satisfaction and to analyze the impact of service quality, perceived price, corporate image, customer satisfaction on consumer loyalty. This research uses seven hypotheses. The population in this study is that consumers in Matahari department store Paragon City Mall Semarang. The sample in this study as many as 100 people. The sampling technique used purposive sampling. The criteria for the sample in this study is consumers who buy and be at least 17 years of age. The analysis tool used is multiple linear regression. The results of the analysis can be concluded that: Quality of service is a positive effect on customer satisfaction. Perception prices positively affects customer satisfaction. The company's image positively affects customer satisfaction. Quality of service is a positive effect on customer loyalty. Perception prices positive effect on customer loyalty. The company's image a positive effect on customer loyalty. Consumer satisfaction has positive effect on consumer loyalty. Customer satisfaction does not mediate the effect of service quality on customer loyalty. Customer satisfaction does not mediate the effect of price perception on consumer loyalty. Customer satisfaction does not mediate the influence of corporate image on customer loyalty. Keywords: service quality, perceived price, corporate image, customer satisfaction and customer loyalty